Charting a roadmap for heart failure research in India: Insights from a qualitative survey - Sivadasanpillai Harikrishnan; Linda Koshy; Sanjay Ganapathi; Panniyammakal Jeemon; Raman Krishna Kumar; Adrija Roy; S. Reethu; Surya Ramachandran; L. R. Lakshmikanth; Meenakshi Sharma; Vijay Kumar Chopra (Indian Journal of Medical Research, 2023)
This study aims to identify the lacunae and to suggest recommendations to improve HF research.
Keywords: Global policy database; Health policy survey; Reproductive health; Maternal and newborn; Child and Adolescent; Health policy database